The Influence of Supervision on Employee Performance at PT. Persada Technical Media - Zulpedri, Zulpedri; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of supervision on employee performance at PT. Persada Technique. This research was conducted using a causal associative quantitative approach. The sample used was all company employees, with a total of 61 people. The research results show that supervision has a positive and significant effect on employee performance. This is shown by the T-count value of 3.193 which is greater than the T-table 11.818 > t table 1.67109, with a significance value of 0.000 < 0.05. The regression coefficient shows that if supervision is increased by 1 unit, employee performance will increase by 1,709 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.698 or 69.80%, which indicates that supervision has a low influence on employee performance, while the remaining 30.20% is influenced by other factors that have not been studied. Thus, partially, supervision has a positive and significant effect on employee performance at PT. Persada technique. This identifies that, meaning, improvements in Supervision can contribute to improving employee performance.